The influence of bronchial asthma control level on the quality of life indices - Herasymova, O. V.; Protsiuk, T. L.; Protsiuk, L. O.; Surkova, N. M.; Kotsur, L. D.; Kuleshov, O.V. (Pathologia, 2018)
Objective: to study the indices of general and specific quality of life in schoolchildren, depending on the level of bronchial asthma control. Materials and methods: Quality of life parameters of 189 in-patients with BA, aged 6–17 years and 95 controls were studied. Parallel questioning with subsequent analysis of quality of life indices in 189 parents of BA children and 95 parents of the control group children was performed. General QL was evaluated using РedsQL (Pediatric Quality of Life Inventory 4.0). Specific quality of life was evaluated using specific quality of life questionnaire for the children ill with bronchial asthma – PAQLQ (Pediatric Asthma Quality of Life Questionnaire). Statistical analysis of the data obtained was done by variance statistical methods using the standard program package of multivariate statistical analysis Statistica 6.0 Results. The study found the index of physical functioning to be 43.6 [31.3–62.5] points in the children with UC BA, 53.1 [37.5–68.2] points in those with PC BA, being significantly lower as compared to the control group children – 79.6 [56.0–100.0] points (P < 0.001). Рhysical functioning index in the children with UC BA was 1.7 times lower as compared to those with C BA. Comparison of the indices in those with PC BA – 53,1 [37.5–68.2] points and C BA – 74.1 [50.0–76.0] points, showed that physical activity in the children with PC BA was significantly lower as compared to those with C BA (P < 0.001). The analysis showed no significant difference between the answers of the children with asthma and their parents. No significant difference between the answers of healthy children’s parents and the children themselves was revealed as well (P > 0.05). The cumulative index of QL was dependent on the level of BA control. It was 2.5 [1.4–3.6] points in the children with UC BA, being significantly lower as compared to those with PC BA – 3.9 [2.8–4.9] points, and C BA – 6.2 [5.6–6.8] points (р<0.001); and in the children with PC BA this index was significantly lower as compared to those with C BA (P < 0.01). Conclusions. Along with traditional methods of assessment of respiratory function and laboratory indices of inflammatory process activity in bronchial asthma, study of physical and mental health, social activity, general well-being and many other parameters of quality of life, as well as the influence of treatment on these parameters should be carried out.